Makna dalam Lirik Lagu “Nina” Karya Adnan Satyanugraha Putra (.Feast) - Zahiya Zahiya; Dwi Wahyu Candra Dewi (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
The purpose of this study was to find out the meaning with the semiotic approach of Roland Barthes, that is, the meaning of denotations, connotations, and myths in the lyrics of the song “Nina” by Adnan Satyanugraha Putra which comes from the music group .Feast. The method applied in the research is a descriptive qualitative method by describing the results of the research through words. The objects in this study are two: material objects in the form of song lyrics and formal objects in the form of meaning of song lyrics. Data analysis techniques in this study were performed using auditory observation techniques by observing sounds in music and data analysis by analyzing song lyrics in each stanza. The results of this study found a deep meaning about the feelings of a father who loves his daughter very much..